EFEKTIVITAS TERAPI AKUPRESUR PADA KEADAAN KADAR GULA DARAH PADA PASIEN DIABETES MELITUS TIPE 2 - Hasan Nidlom (Journal of Innovation Research and Knowledge, 2024)
Diabetes mellitus refers to a group of diseases that affect the way the body uses blood sugar (glucose). Glucose is an important energy source for the cells that form muscles and tissue. It is also the brain's main source of fuel. The main causes of diabetes vary based on the type. But whatever type of diabetes you have, it can cause excess sugar in the blood. Too much sugar in the blood can cause serious health problems. Quasy Experimental research design with a one group pre test and post test design. Place and time of research in Dermo sub-district, Bangil Health Center working area from May to June 2024. The population of type 2 diabetes mellitus patients was 89 people with a sample of 11 people using simple radom sampling method. The data was processed computerized and analyzed using univariate statistics and bivariate analysis using the Wilcoxon test. The results of the study showed that the average blood sugar level before acupressure therapy was 234.45 mg/dL. The average blood sugar level after acupressure therapy was 219.91 mg/dL. The Wilcoxon test was obtained with a value of p = 0.001 (p<0.05).